The Association of Child Abuse Experiences and Intolerance of Uncertainty in Young Adults - Dirican, Ayse Hatun; Kozak, Ekin Doga; Kavakci, Onder; Sonmez, Berna (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
Objective: Drawing upon the identity disruption model, we investigated the association between child abuse experiences (emotional, physical, and sexual) and intolerance of uncertainty. We also addressed demographic differences in uncertainty intolerance in this study. Methods: Using online survey questionnaires, we collected data from a sample of 302 young adults in Turkey. The data were analyzed using confirmatory factor analysis, structural equation modeling, one-way analysis of variance, and independent samples t-test. Results: The results showed that of the three types of child abuse analyzed, only emotional abuse was significantly and positively associated with intolerance of uncertainty. In contrast, age was negatively associated with intolerance of uncertainty. Regarding demographic differences, we found that the level of intolerance of uncertainty differed based on young adults' gender, psychiatric diagnosis, and education. Specifically, our findings indicated that intolerance of uncertainty is significantly higher in females compared to males. It is also significantly higher in young adults with a diagnosis for psychiatric disorders than those without. Moreover, intolerance of uncertainty is significantly higher in young adults who have a high school graduate degree than their undergraduate and graduate counterparts. We discussed how child abuse is associated with heightened intolerance of uncertainty in young adulthood as well as why demographic differences may exist in uncertainty intolerance. Conclusions: The present study expanded the existing research on the psychological consequences of childhood abuse experiences by linking child abuse to intolerance of uncertainty. Particularly, exposure to emotional abuse in early life can be a risk factor to cope with uncertainty in later life.
Keywords: ANXIETY DISORDERS; MODEL; DEPRESSION; SYMPTOMS; WORRY; DISTRESS; TRAUMA; COMORBIDITY; RELIABILITY; SENSITIVITY; Psychiatry